Perlis sunshine mango seed flour body scrub: product development for antioxidant properties and sensory evaluation - Kho, Sy Xuan (School of Bioprocess Engineering, University Malaysia Perlis, 2017)
The utilization of Perlis Sunshine Mango Seed Flour (MSF) is introduced as natural active ingredient in body scrub for skin care cosmetology. In this study, the body scrubs had been prepared in different types of form, there were rough salt and oil-in-water (O/W) emulsion form. Both type of body scrub had formulated as based and containing Perlis Sunshine MSF. The determination of total phenolic content (FC-reagent method), ascorbic acid content (HPLC) and total antioxidant activity (DPPH method) of the body scrubs were evaluated for the possible application in dermo-cosmetic field. The results appeared that O/W MSF body scrub shown the best results among other body scrubs except for the determination of ascorbic acid content. The O/W MSF body scrub extract contains 6.65 0.16 GAE mg/g of total phenolic content (TPC) with 32.29 2.60% of DPPH activity inhibition. However, the homemade MSF body scrub extract had shown greater area under the peak and the height of peak was higher if compared to O/W MSF body scrub extract in determination of ascorbic acid content. For the sensory analysis, most of the body scrubs testers satisfied with the body scrubs in O/W body scrubs compared to rough salt body scrubs in all the attributed tested.